Analytical chemistry laboratory manual - Zuraini Abdullah Munir; Zaini Hamzah; Sabarina Md Yunus (UiTM Press, 2014)
This manual contains a total of eleven laboratory experiments that are divided into four main topics. Those experiments will enable students to appreciate Analytical chemistry and value its importance in the field of chemistry